Modern approaches to the treatment of idiopathic epiretinal membrane - V.A. Bogdanova; R.R. Fayzrakhmanov; O.A. Pavlovskiy; E.D. Bosov (РМЖ "Клиническая офтальмология")
V.A. Bogdanova, R.R. Fayzrakhmanov, O.A. Pavlovskiy, E.D. Bosov Pirogov National Medical and Surgical Center, Moscow, Russian Federation Epiretinal membrane (ERM) is one of the most prevalent ocular pathologies. ERM has been observed in cases of uveitis, retinal detachment, and diabetic retinopathy. In some cases, however, the underlying cause cannot be determined, and the condition is classified as idiopathic. The severity of the course of ERM varies considerably, from asymptomatic to severe vision loss and metamorphopsia. The classification is based on three factors: the density of the fibrous tissue, the severity of the retinal lesions, and the associated biomicroscopic signs. The aim of this article is to review the current approaches to the management of idiopathic ERM. Currently, surgery is the only universally accepted treatment for idiopathic ERM. However, there are a number of peculiarities of surgery that significantly affect the final outcome and further prognosis. In particular, patients often have unsatisfactory postoperative recovery of visual function, which requires revision of the strategy of minimally invasive interventions and refinement depending on the pathomorphology and structural features of the retina. Keywords: epiretinal membrane, internal limiting membrane, membrane peel, retina, vitreoretinal surgery, minimally invasive interventions. For citation: Bogdanova V.A., Fayzrakhmanov R.R., Pavlovskiy O.A., Bosov E.D. Modern approaches to the treatment of idiopathic epiretinal membrane. Russian Journal of Clinical Ophthalmology. 2024;24(3):133–137 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-6.